2022
DOI: 10.1002/pd.6087
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid‐derived stem cell potential for therapeutic and surgical use: A review of the literature

Abstract: Objective Spina bifida is a debilitating neutral tube defect affecting many infants. The impact and severity of spina bifida depends on whether the patient exhibits a closed defect, spina bifida occulta, or an open defect, spina bifida aperta. Patients with spina bifida have physical and mental disabilities which merit further research into less invasive, more successful treatments. In addition to serving as protection for the growing fetus and facilitating nutrient exchange, amniotic fluid (AF) is a rich sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…AF-MSCs are a mixed population of stem cells that have also shown promising data among different therapeutic and surgical applications. They express both adult and embryonic cell markers, indicating their stage is between embryonic and adult phenotype, which allows them to differentiate into cells of all three germ layers, including hepatic, myogenic, osteogenic, and neurogenic cell types [ 19 , 20 , 21 ]. P-MSCs can be isolated from chorionic villi early in gestation or at the time of birth.…”
Section: Mesenchymal (Stromal) Stem Cellsmentioning
confidence: 99%
“…AF-MSCs are a mixed population of stem cells that have also shown promising data among different therapeutic and surgical applications. They express both adult and embryonic cell markers, indicating their stage is between embryonic and adult phenotype, which allows them to differentiate into cells of all three germ layers, including hepatic, myogenic, osteogenic, and neurogenic cell types [ 19 , 20 , 21 ]. P-MSCs can be isolated from chorionic villi early in gestation or at the time of birth.…”
Section: Mesenchymal (Stromal) Stem Cellsmentioning
confidence: 99%
“…Remarkably, AFSCs do not have the same detrimental effects as embryonic stem cells (ESCs) and adult stem cells ( 26 ). Moreover, they show greater immunosuppressive function and are capable of greater maintenance of pluripotency ( 27 ). Furthermore, AFSCs are not bound by the legal and ethical limitations that ESCs are subject to.…”
Section: Discovery Of Amniotic Fluid Stem Cell Potential In Necmentioning
confidence: 99%
“…The general quality of AFSC cultures is significantly correlated with gestational age of the fetus when AF is harvested. In studies with experimental spina bifida patients, MSCs and neural SCs show to have been affected by gestational age ( 27 ). Recent studies with AFSCs show a similar trend, however gestational age is shown to affect paracrine signalling capabilities.…”
Section: Challenges Of Clinical Translation Of Afsc-based Therapy In ...mentioning
confidence: 99%
See 2 more Smart Citations